2019
DOI: 10.3390/microorganisms7120598
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Filtering Drives the Assembly of Habitat Generalists and Specialists in the Coastal Sand Microbial Communities of Southern China

Abstract: Coastal sands harbor diverse microbial assemblages that play a critical role in the biogeochemical cycling of beach ecosystems. However, little is known about the relative importance of the different ecological processes underlying the assembly of communities of sand microbiota. Here, we employed 16S rDNA amplicon sequencing to investigate the sand microbiota of two coastal beaches, in southern China. The results showed that sand microbial assemblages at intertidal and supratidal zones exhibited contrasting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 59 publications
4
13
0
Order By: Relevance
“…Instead, however, fungal and protist communities had the largest unexplained variance and edaphic properties played the most important role on the alpha and beta diversity of all groups. This is in accordance with other studies on microbial communities which have actually shown that biogeographic patterns among generalist microbial assemblages might be better explained by environmental conditions than for specialists, suggesting that environmental processes significantly influence all taxa and not only specialists [96][97][98][99][100].…”
Section: Discussionsupporting
confidence: 93%
“…Instead, however, fungal and protist communities had the largest unexplained variance and edaphic properties played the most important role on the alpha and beta diversity of all groups. This is in accordance with other studies on microbial communities which have actually shown that biogeographic patterns among generalist microbial assemblages might be better explained by environmental conditions than for specialists, suggesting that environmental processes significantly influence all taxa and not only specialists [96][97][98][99][100].…”
Section: Discussionsupporting
confidence: 93%
“…Instead, however, fungal and protist communities had the largest unexplained variance and edaphic properties played the most important role on the alpha and beta diversity of all groups. This is in accordance with other studies on microbial communities which have actually shown that biogeographic patterns among generalist microbial assemblages might be better explained by environmental conditions than for specialists, suggesting that environmental processes signi cantly impact all taxa and not only specialists (Székely & Langenheder, 2014, Lindh et al, 2016, Hu et al, 2019, Luo et al, 2019. Future studies could also explore how the environmental niche varies, within a same taxonomic group, between distinct functional groups (e.g.…”
Section: Niche Specialisationsupporting
confidence: 90%
“…In order to assess the enriching effect by lactate-feeding and TCE-supplementing, and explore the microbial community succession patterns during the enriching process, the indicator OTUs for these communities were classified using IndVal analysis with the R package labdsv tool [ 48 ]. Only OTUs with highly significant indicator values (IndVal index >0.95, p < 0.001) were considered strict habitat specialists [ 49 ]. Principal coordinate analysis (PCoA) was used to visualize the β -diversity pattern of the microbial communities based on Bray–Curtis distance matrices.…”
Section: Methodsmentioning
confidence: 99%